2016
DOI: 10.1021/acs.est.6b00562
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Fe(II) Oxidation, Biogenic Lepidocrocite Formation, and Arsenic Immobilization by Pseudogulbenkiania Sp. Strain 2002

Abstract: An anaerobic nitrate-reducing Fe(II)-oxidizing bacterium, Pseudogulbenkiania sp. strain 2002, was used to investigate As immobilization by biogenic Fe oxyhydroxides under different initial molar ratios of Fe/As in solutions. Results showed that Fe(II) was effectively oxidized, mainly forming lepidocrocite, which immobilized more As(III) than As(V) without changing the redox state of As. When the initial Fe/As ratios were kept constant, higher initial Fe(II) concentrations immobilized more As with higher Asimmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 71 publications
6
32
0
Order By: Relevance
“…The dominant genera enriched in the treatments with Fe(II) (Fig. 5) contained more genera that have documented ad FeOB in previous studies (Emerson et al, 2010;Swanner et al, 2011;Shelobolina et al, 2012;Xiu et al, 2016;Hassan et al, 2016) than the agarose only incubations, confirming the effectiveness of the gradient tube in enriching potential microaerophilic FeOB. Many of these microaerophilic FeOB can produce extracellular organic fibers, forming twisted stalks or sheaths and acting as a precipitation template for iron oxides in order to avoid encrustation (Schädler et al, 2009), while others do not produce such structures (Swanner et al, 2011).…”
Section: Fe(ii) Oxidation With Microaerophilic Fe(ii)-oxidizing Bacteriasupporting
confidence: 76%
See 2 more Smart Citations
“…The dominant genera enriched in the treatments with Fe(II) (Fig. 5) contained more genera that have documented ad FeOB in previous studies (Emerson et al, 2010;Swanner et al, 2011;Shelobolina et al, 2012;Xiu et al, 2016;Hassan et al, 2016) than the agarose only incubations, confirming the effectiveness of the gradient tube in enriching potential microaerophilic FeOB. Many of these microaerophilic FeOB can produce extracellular organic fibers, forming twisted stalks or sheaths and acting as a precipitation template for iron oxides in order to avoid encrustation (Schädler et al, 2009), while others do not produce such structures (Swanner et al, 2011).…”
Section: Fe(ii) Oxidation With Microaerophilic Fe(ii)-oxidizing Bacteriasupporting
confidence: 76%
“…strain GE-1, Pseudogulbenkiania sp. strain 2002, Acidovorax sp., and Rhodobacter ferrooxidans strain SW2 and strain KS (Hohmann et al, 2009;Xiu et al, 2015Xiu et al, , 2016.…”
Section: Fe(ii) Oxidation With Microaerophilic Fe(ii)-oxidizing Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…The quantification of extracted Fe is commonly done using spectrophotometric assays (Braunschweig et al 2012;Verschoor & Molot 2013) based on agents such as ferrozine (Stookey 1970) or phenanthroline (Clark 1962 (Stookey 1970;Kundra et al 1974) or high concentrations of Fe III diss (Im et al 2013 It was therefore suggested by Klueglein & Kappler (2013) to replace HCl with sulfamic acid for Fe extraction in samples potentially containing nitrite. Fe extraction using sulfamic acid has proven to be successful in lab systems such as culture media as well as for environmental samples (Li et al 2015;Laufer et al 2016a;Robertson et al 2016;Xiu et al 2016). In this study, we show that when analyzing Fe-spiked fresh water sediments we discovered that high carbonate contents of the sediments strongly interfered with the extraction of Fe using sulfamic acid as extractant.…”
Section: Introductionmentioning
confidence: 70%
“…silicates or metals other than Fe) can interfere with the Fe analysis (Kundra et al 1974;Anastácio et al 2008;Im et al 2013) yet also Fe extraction can be affected as shown for intermediate reaction products of the denitrification process (Klueglein & Kappler 2013;Yan et al 2015). Apart from the commonly used separation of solid and liquid phase prior to Fe extraction (Weber et al 2006;Chakraborty et al 2011), the protocol suggested by Klueglein & Kappler (2013), using 40 mM sulfamic acid instead of 1 M HCl as extracting agent has been proven to be highly efficient and quantitatively accurate for the extraction of poorly crystalline Fe from bacterial batch cultures containing nitrite (Klueglein & Kappler 2013;Klueglein et al 2015;Li et al 2015;Xiu et al 2016) and was successfully applied to sediment and slurry samples (Laufer et al 2016a;Robertson et al 2016).…”
Section: Implications and Recommendation For Protocol Applicationmentioning
confidence: 99%